KARAKTERISASI GUGUS FUKOIDAN DAN AKTIVITAS ANTIOKSIDAN EKSTRAK FUKOIDAN RUMPUT LAUT Sargassum sp ASAL PERAIRAN LEMUKUTAN, KALIMANTAN BARAT, INDONESIA - Risdo Sahputra Sinaga; Warsidah Warsidah; Shifa Helena (Program Studi Ilmu Kelautan FMIPA Universitas Tanjungpura, 2022)
Sargassum sp contains fucoidan compounds that have potential to be natural antioxidants. Fucoidan is a complex sulfate polysaccharide derived from brown seaweed through extraction processes. The purpose of this study was to determine the characteristics of functional groups and antioxidant activity of fucoidan compounds Sargassum sp from Lemukutan Island, West Kalimantan, Indonesia. Extraction of fucoidan compounds from Sargassum sp was carried out using ethanol solvent at 71°C temperature for 2 hours, re-extracted with cold water as much as 25 ml, and heated at 250°C temperature for 2 hours. Characterization of fucoidan functional groups using FT-IR and determination of antioxidant activity using the DPPH method. The results showed fucoidan yield was 10.67%. Based on FT-IR showed carbohydrate group, sulfate group, fucosal group, and monosaccharide group. At 300 ppm concentration, the antioxidant activity produced was 11.14%, IC50 (Inhibition Concentration 50) of the fucoidan antioxidant sargassum sp seaweed was more than 300 ppm and classified as a weak antioxidant. Keywords: Fucoidan; Sargassum sp; DPPH; FT-IR (Fourier Transform Infrared)